PEMANFAATAN INTERNET SEBAGAI PELUANG MENGEMBANGKAN USAHA - Haryoko, Ugeng Budi; Juhaeri, Juhaeri; Dana, Dana; Susanti, Novia; Sunardi, Didi (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Setting up a business is a tempting idea for some people, whether on a small or large scale. In building a business, the right marketing strategy is needed so that the business can flourish. In addition, it must also adjust to the budget that is owned. If you don't have too much budget, it might be better to open a small business before finally turning it into a large-scale business. This dedication is titled Utilizing the Internet as a Business Opportunity to Develop Businesses. The purpose of community service is to provide training on how to take advantage of business opportunities by using the internet at the 83rd Junior High School in Jakarta. The method of implementing this service is carried out in several activities, namely by involving many parties, including teachers, students and employees of the Jakarta 83 Junior High School Cooperative. The conclusion of community service (PKM) is that in general community service activities can be carried out well and received and received support from the Jakarta 83 Junior High School Cooperative, so that awareness can be created on the importance of increasing the Cooperative marketing network in improving its business in internet utilization.